Urgensi Kompetensi Pribadi Bagi Calon Konselor dalam Mewujudkan Pelayanan yang Prima - Muwakhidah Muwakhidah; Hartono Hartono; Ryandika Firmasyah; Nur Syamsiah (Universitas Negeri Malang, 2023)
Abstract: Implementationally, the role of counselors in practice guidance and counseling services in schools is actually inseparable from the problem of competence counselor. Counselor's competency issues refer to the ability of the counselor, particularly the personal competence of the counselor. Problems concerning true personal competence are not only experienced by counselors, but student college also experience such a thing. The process of implementing counseling that seems